ASME steam tables, Compact edition properties of saturated and superheated steam in U.S. customary and SI units from the IAPWS-IF97 International Standard for Industrial Use (CRTD (Series), 2006)
Properties of Saturated and Superheated Steam in U.S. Customary and SI Units from the IAPWS-IF97 International Standard for Industrial Use. This is an updated and concise booklet